An Innovative Technology for Monitoring the Distribution of Abutment Stress in Longwall Mining - Zhibiao Guo; Weitao Li; Songyang Yin; Dongshan Yang; Zhibo Ma (Energies, 2021)
Fracturing roofs to maintain entry (FRME) is a novel longwall mining method, which has been widely used in China, leading a new mining revolution. In order to research the change law of side abutment pressure and movement law of overlying strata when using the FRME, a new abutment pressure monitoring device, namely, the flexible detection unit (FDU), is developed and is applied in the field. The monitoring results show that compared with the head entry (also called the non-splitting entry), the peak value of the lateral abutment pressure in the tail entry (also termed the splitting entry) is reduced by 17.2% on average, and the fluctuation degree becomes smaller. Then, finite difference software FLAC3D is used to simulate the stress change of the solid coal on both sides of the panel. The simulation results show that the side abutment pressure of the tail entry decreases obviously, which is consistent with the measured results. Comprehensive analysis points out that after splitting and cutting the roof, the fissures can change the motion state of the overlying strata, causing the weight of the overburden borne by the solid coal to reduce; therefore, the side abutment pressure is mitigated.